DNA methylation signatures of alcohol use disorder: a large-scale meta-analysis in the Psychiatric Genomics Consortium - Zillich, Lea; D’Augello, Sofia; Avetyan, Diana; Delgado Gonzales de Kleber, Graciela; Gizer, Ian R.; Jung, Jeesun; Katrinli, Seyma; Kleber, Marcus E.; Merrill, Natalie; Moissl-Blanke, Angela P.; Núñez-Rios, Diana L.; Otto, Jacqueline M.; et al. (medRxiv, 2025)
Despite extensive research on DNA methylation (DNAm) signatures associated with alcohol use disorder (AUD), findings are often inconsistent and not replicated. We conducted a large-scale meta-analysis of epigenome-wide association studies (EWAS) to identify reliable, reproducible epigenetic markers of AUD. - Seven cohorts, comprising 3,775 individuals (1,325 with AUD), contributed to this meta-analysis within the framework of the Psychiatric Genomics Consortium Substance Use Disorders Epigenetics Working Group. Downstream analyses included the identification of differentially methylated regions, overrepresentation analyses, and the construction of a methylation risk score (MRS). - We identified 118 significant CpG sites associated with AUD, with the strongest association found at cg24889777 (p=5.12×10-17) in the long non-coding RNA LOC100505942. CpG sites were enriched for pathways related to GTPase signaling and transmembrane transporter activity, as well as EWAS signals of alcohol consumption. The MRS explained 10.44% of variance in heavy drinking in an independent cohort (N=2,534, AUC=0.657). - This large-scale meta-analysis offers key insights into the epigenetic mechanisms of AUD and lays the groundwork for future research on methylation risk scores for the diagnosis, prognosis, and treatment in AUD.